New Acyclic Triterpenoid Glycoside Constituent from the Fruits of Lycium chinense - A. Siddiqui, Nasir; Chung, Ill-Min; Nagella, Praveen; Ali, Mohd; Alam, Perwez; Ahmad, Ateeque (Asian Journal of Chemistry, 2014)
One new acyclic triterpenoid constituent as 14,18,22-trimethyl 3a,5a,17a,19a,22a- pentahydroxytetracosan-25,26,27-trioic acid-3a-O-a-L-glucofuranosyl-(6a®1'a)-O-a-L-glucopyranosyl-(6'a®1''a)-O-a-L-glucopyranoside-5a-O-a-L-glucofuranosyl-(6b®1'b)-O-a-L-glucopyranosyl-(6'b®1''b)-glucopyranoside-17a-O-L-glucopyranosyl-(6c®1'c)-O-Lglucopyranosyl-(6'c®1''c)-O-L-glucopyranoside-19a-O-L-glycopyranosyl-(6d®1'd)-O-a-L-glucopyranosyl-(6'd®1''d)-O-a-L-glucopyranoside (1) was isolated and identified from the fruits of Lycium chinense. The chemical structure of the new compound was elucidated by 1D and 2D NMR spectroscopic techniques (COSY, HMBC and HSQC) aided by FAB mass and IR spectra.